(untitled) (Research, Society and Development, 2020)
Sugarcane has great socioeconomic importance, due to the generation of jobs, and because it is a raw material for several products. Therefore, it is essential to carry out the proper nutritional management, mainly of nitrogen (N), in order to benefit the productivity of the crop. The objective of the work was to evaluate the development of different varieties of sugarcane cultivated with supply of N via nutritive and leaf solution. The experiment was carried out in a greenhouse at the Federal Institute of Pernambuco - Campus Vitória, using pre-sprouted sugarcane seedlings (MPB), in a randomized block design, with two varieties RB992506 and CTC961007, grown in washed sand in absence and presence of N, with two levels of foliar application of N (with and without), factorial arrangement (2 x 2 x 2), with three replicates. At 53 DAT, evaluations were carried out: stem diameter; plant height; fresh and dry mass of shoot and root; chlorophyll; sheet width and length +1. The complete nutrient solution increased all the variables mentioned above, regardless of the foliar application of N. In general, the foliar application only increased when associated with an incomplete solution. Nitrogen provided better development and increased crop productivity.